Advocacy Impact Evaluation - Patton, Michael Q. (Journal of MultiDisciplinary Evaluation, 2008)
Advocacy and policy change evaluations focus on policy as the unit of analysis rather than the more traditional program or project. Advocacy evaluation, like all evaluation, is guided by the profession’s Principles and Standards. Advocacy evaluation can be, and should be, utilization-focused. That means focusing the evaluation on intended use by intended users, and evaluating the evaluation by that standard.